A comprehensive review of automatic cleaning systems of solar panels. (October 2021) - Farrokhi Derakhshandeh, Javad; AlLuqman, Rand; Mohammad, Shahad; AlHussain, Haya; AlHendi, Ghanima; AlEid, Dalal; Ahmad, Zainab
Abstract: Photovoltaic modules are well-established, commercially accepted systems that have been generating electricity since 1995. The efficiency of solar energy produced by photovoltaic modules can be affected by two main factors: environmental - such as humidity, wind speed, precipitation, and temperature - and non-environmental, which takes into account factors such as atmospheric pollution, dust accumulation, and bird droppings. Dust accumulation, dirt, and bird dropping are some leading causes that lead to the poor functionality of solar panels. This paper reviews the most recent and common cleaning systems designed and fabricated to overcome problems associated with dust accumulation problems. In general, the cleaning systems are categorized into two main groups; i) active and ii) passive. A comprehensive review of the automatic cleaning systems is conducted. The features of each system are explained, and the pros and cons are compared in detail. Leading indicators of the system, including cost, efficiency, water usage, cleaning time, and human interference, are considered when choosing an optimal cleaning system. While brushing and heliotex cleaning systems are cost-effective mechanisms, both require a human operator. On the other hand, electrostatic cleaning systems are recommended for regions where water is scarce. Furthermore, robotic cleaning systems are not recommended for counties with windy climates due to their slow operation and high costs.